The Effects of Rice Washing and Storage of White Rice in Magic Com on Vitamin B1 (Thiamine hydrochloride) Contents - Marieta H. Ilatha; Luther Kadang; Febri O. Nitbani (Journal of Applied Chemical Science, 2013)
There has been conducted the research to know the effect of rice washing and white rice storage in magic com against vitamin B1 (tiamin hydrochloride) contents. The water used in rice washing was tap water and aquadest. The presences of the building block elements of the vitamin B1 in washing water qualitatively indicated the effects of each type of the water, while the contents of the vitamin either in rice or in washing water was determined by UV-Vis spectrophotometer at wave length of 385 nm. The results showed that the sulfur and chlorine elements, the building block elements of the vitamin, were found in tape water but those elements were not found in aquadest. The vitamin contents of the rice in magic com was up to 0.214 mg/kg, the washing water of stage I, II, and III were 0.096, 0.094, and 0.183 mg/L, respectively. Those results conclusively indicate that the elements contained by the washing water determine the presences of the vitamin building block elements in the rice washing water and therefore reduced the vitamin contents of the rice. The more interesting information of this study was reported in the main article.